An Analysis of Earthquake-Resistant Building: Case Study of Earthquake-Resistant House Construction Responding to the Yogyakarta 2006 Earthquake (KRINOK: JURNAL ARSITEKTUR DAN LINGKUNG BINA, 2024)
On May 27, 2006, at 5:58 AM WIB, an earthquake with a magnitude of 5.9 on the Richter scale struck Central Java and its surroundings, causing numerous casualties and building damage. Dusun Ngibikan in Bantul, D.I. Yogyakarta, was one of the affected areas. The residents of Dusun Ngibikan managed to complete the reconstruction within four months without waiting for government assistance, using leftover debris materials. They built 65 houses with constructions that met earthquake-resistant building criteria in accordance with the regulations of the Minister of Public Works. This study employs a qualitative descriptive method to assess the compliance of these constructions with the rehabilitation and reconstruction guidelines for post-earthquake areas in Yogyakarta and Central Java, and the results show that the constructions in Dusun Ngibikan met various established criteria.